2005
DOI: 10.1016/j.jmaa.2004.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Invariant algebraic curves of large degree for quadratic system

Abstract: In this paper we present for the first time examples of algebraic limit cycles and saddle loops of degree greater than 4 for planar quadratic systems. In particular, we give examples of algebraic limit cycles of degree 5 and 6, and algebraic saddle loops of degree 3 and 5 surrounding a strong focus. We also give an example of an invariant algebraic curve of degree 12 for which the quadratic system has no Darboux integrating factors or first integrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 5 publications
0
36
0
Order By: Relevance
“…The second class was found in [16]. More recently, two new classes have been found and in [9] the authors proved that there are no other algebraic limit cycles of degree 4 for quadratic vector fields. The uniqueness of these limit cycles was proved in [11].…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The second class was found in [16]. More recently, two new classes have been found and in [9] the authors proved that there are no other algebraic limit cycles of degree 4 for quadratic vector fields. The uniqueness of these limit cycles was proved in [11].…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 98%
“…The uniqueness of these limit cycles was proved in [11]. It is known that there are quadratic polynomial differential systems having algebraic limit cycles of degree 5 and 6, see [9], and that this limit cycle is the unique one for these differential systems. Other results on algebraic limit cycles can be found in [20].…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Chavarriga et al [29] have found all the cases of algebraic limit cycles of degree 4 for quadratic polynomial systems and Chavarriga, Giacomini and Llibre [16] have proved their uniqueness. Christopher et al [38] have given examples of quadratic systems with an algebraic limit cycle of degree 5 and 6. The fact that these limit cycles are hyperbolic is proved in [64].…”
Section: Limit Cycles and Hilbert's 16th Problemmentioning
confidence: 99%
“…It is shown in [9] that there are no algebraic limit cycles of degree 3 for a quadratic system. In [13], two examples of quadratic systems with an algebraic limit cycle of degree 5 and 6 are described. We will show that none of these quadratic systems has a Liouvillian first integral.…”
Section: Quadratic Systems With An Algebraic Limit Cyclementioning
confidence: 99%
“…In a work due to C. Christopher, J. Llibre and G.Świrszcz [13] two families of quadratic systems with an algebraic limit cycle of degrees five and six, respectively, are given. These two families are constructed by means of a birrational transformation of system (21).…”
Section: Quadratic Systems With An Algebraic Limit Cyclementioning
confidence: 99%